Characterization of calcium carbonate extracted from eggshell waste at various calcination temperature - Najah, M. I.; Razak, Aisyah; Che Shukur Nekmat, Nor Aida; Adzila, Sharifah; Othman, Raudhah; Nordin, Normayati (WARSE, 2020)
An efficient method to waste utilization is to successfully transform it into high value products. Chicken eggshell contain potential useful minerals of calcium carbonate in which can be processed into biomaterials used in biomedical application. The objective of this study is to derived calcium carbonate from eggshell and analyze the effect of various calcination temperatures on the properties of calcium carbonate. Fourier transform infrared (FTIR) spectroscopy indicates that all calcined samples reveals calcium carbonate is no longer present after calcination as it is already converted to calcium oxide. This also supported by x-ray diffraction (XRD) graphs notably on 900°C. Scanning electron microscopy (SEM) and particle size analysis are applied to determine morphological properties and mean sizes of particles for both raw and calcined samples.